2013
DOI: 10.1080/13603116.2012.752877
|View full text |Cite
|
Sign up to set email alerts
|

Embedding learning in a paediatric hospital: changing practice and keeping connected

Abstract: This paper, the final paper in the Keeping Connected special issue, presents the key findings of the overall study and focuses on the challenging process of re-imagining a hospital setting as a community of learning for young people in light of these findings. The paper focuses on young people as learners within the overarching themes emanating from the Keeping Connected research such as normalcy, diversity and communication. Taking up Slee's notion of 'the irregular school', we describe how one setting in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
2
20
0
3
Order By: Relevance
“…Thus, hospitalized school-age youngsters deserve access to education while they are away from school ( 21 ). Not only education constitutes a right, but also this educational experience is likely to provide inpatients with some sense of normalcy, and help in their recovery ( 22 ). When hospitals provide inpatients with a connection to their school lives, it helps them maintain a sense of normalcy [e.g., ( 23 )], it appeases the child and parents' worries related to school learning, and prepares the child for school re-entry after discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hospitalized school-age youngsters deserve access to education while they are away from school ( 21 ). Not only education constitutes a right, but also this educational experience is likely to provide inpatients with some sense of normalcy, and help in their recovery ( 22 ). When hospitals provide inpatients with a connection to their school lives, it helps them maintain a sense of normalcy [e.g., ( 23 )], it appeases the child and parents' worries related to school learning, and prepares the child for school re-entry after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…When hospitals provide inpatients with a connection to their school lives, it helps them maintain a sense of normalcy [e.g., ( 23 )], it appeases the child and parents' worries related to school learning, and prepares the child for school re-entry after discharge. Moreover, education can provide youngsters with opportunities to maintain their connections with their lifeworld beyond the hospital wards, which can also ensure the support from their teachers, schools, and classmates ( 22 ). In fact, hospitalized children are more likely to be engaged in school when their counterparts and the class teacher preserve them in their minds in spite of their absence in school ( 24 ) (e.g., maintain contact sending drawings, recovering cards, text messages, or notebooks with school activities and homework to be completed).…”
Section: Introductionmentioning
confidence: 99%
“…In order to address the complexities of maintaining educational engagement and progress in the hospital setting, teachers at the Royal Children's Hospital (RCH) in Melbourne, Australia, decided to incorporate a stronger focus on personalised learning within an existing project‐based learning environment (Hopkins et al, ). A key decision in the process of adopting a more personalised learning model was to take an EIP approach to the development and implementation of individual learning plans (ILPs) for every priority patient.…”
Section: Undertaking Eip In a Paediatric Setting: A Real World Examplementioning
confidence: 99%
“…This inclusion of the ILP in the child's medical record is thought to be the first time in Australia that such educational information has been included in the legal medical record, and constitutes a significant shift in hospital policy regarding the whole‐child‐centred approach to care. This shift in thinking helps to re‐position young people with health conditions from being ‘patients’ to also being ‘learners’ (Hopkins et al, ). It also articulates the possibility of re‐positioning hospitals from being seen purely as health care spaces to being conceptualised as young‐person‐centred institutions that are engaging settings within which rich learning can occur (Zazryn et al, ).…”
Section: Undertaking Eip In a Paediatric Setting: A Real World Examplementioning
confidence: 99%
“…Previous studies have found that video may improve social presence by providing an audio and visual connection, especially for remote students (Weiss, Whiteley, Treviranus, & Fels, ; Wilkie, ). Keeping in contact using technology helped them feel more confident about their reintegration into school and about their future (Hopkins, Moss, et al., ; Yates, ).…”
Section: Introductionmentioning
confidence: 99%